Managing Legitimacy: Strategic and Institutional Approaches - Suchman, Mark C. (Academy of Management Review, 1995)
This article synthesizes the large but diverse literature on organizational legitimacy, highlighting similarities and disparities among the leading strategic and institutional approaches. The analysis identifies three primary forms of legitimacy: pragmatic, based on audience self-interest; moral, based on normative approval: and cognitive, based on comprehensibility and taken-for-grantedness. The article then examines strategies for gaining, maintaining, and repairing legitimacy of each type, suggesting both the promises and the pitfalls of such instrumental manipulations.